2012
DOI: 10.2135/cropsci2011.07.0373
|View full text |Cite
|
Sign up to set email alerts
|

Timing and Frequency Effects of Lightweight Rolling on Dollar Spot Disease in Creeping Bentgrass Putting Greens

Abstract: Dollar spot (DS) (Sclerotinia homoeocarpa F.T. Bennett) is an important disease on golf course turfgrasses in the United States. The objective of this study was to elucidate disease reduction mechanisms related to lightweight rolling. Creeping bentgrass (Agrostis stolonifera L.) plots that were subjected to daily (5 d wk−1) rolling treatments (1x a.m., 1x p.m., 2x a.m.) showed significant DS reductions when compared with a nonrolled control. Treatments rolled in the afternoon (after dew and guttation fluid dis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

3
12
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 15 publications
3
12
0
Order By: Relevance
“…Turfgrass cultural practices, such as proper nitrogen fertility and irrigation, are commonly used to reduce dollar spot symptoms in a turfgrass sward. The removal of guttation fluids with dew whips or the use of lightweight rollers can also reduce disease severity (Giordano et al, 2012). Chemical and biological fungicides are also tools used to manage dollar spot (Walsh et al, 1999).…”
mentioning
confidence: 99%
“…Turfgrass cultural practices, such as proper nitrogen fertility and irrigation, are commonly used to reduce dollar spot symptoms in a turfgrass sward. The removal of guttation fluids with dew whips or the use of lightweight rollers can also reduce disease severity (Giordano et al, 2012). Chemical and biological fungicides are also tools used to manage dollar spot (Walsh et al, 1999).…”
mentioning
confidence: 99%
“…operations (Giordano et al, 2012;Nikolai et al, 2001). Studies have shown that sand textured (80% sand, 10% peat, 10% soil) plots that were rolled had increased percentage of water retention in comparison with the nonrolled plots (Nikolai et al, 2001).…”
Section: Discussionmentioning
confidence: 99%
“…Studies have shown that sand textured (80% sand, 10% peat, 10% soil) plots that were rolled had increased percentage of water retention in comparison with the nonrolled plots (Nikolai et al, 2001). Therefore, mechanisms by which rolling is suppressive to the dollar spot pathogen could be the effect of soil moisture levels mitigating drought-stress-related disease epidemics (Couch, 1966;Couch and Bloom, 1960;Dykema, 2014), or the effect of beneficial microorganisms that proliferate in the turfgrass edaphic environment, as proposed by Giordano et al (2012). Moreover, our observations support earlier statements that drought-stressed turf is more susceptible to a variety of turf diseases that, in effect, cause a noticeable decrease of turfgrass quality (Couch, 1966;Couch and Bloom, 1960).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations